Carnosic Acid Alleviates Levodopa-Induced Dyskinesia and Cell Death in 6-Hydroxydopamine-lesioned Rats and in SH-SY5Y Cells - Lai, Chun-Yi; Lin, Chia-Yuan; Wu, Chi-Rei; Tsai, Chon-Haw; Tsai, Chia-Wen (Frontiers in Pharmacology, 2021)
The present study investigated the impact of carnosic acid (CA) from rosemary on the levodopa (L-dopa)-induced dyskinesia (LID) in rats treated with 6-hydroxydopamine (6-OHDA). To establish the model of LID, 6-OHDA-lesioned rats were injected intraperitoneally with 30 mg/kg L-dopa once a day for 36 days. Rats were daily administrated with 3 or 15 mg/kg CA by oral intubation prior to L-dopa injection for 4 days. Rats pretreated with CA had reduced L-dopa-induced abnormal involuntary movements (AIMs) and ALO scores (a sum of axial, limb, and orofacial scores). Moreover, the increases of dopamine D1-receptor, p-DARPP-32, ΔFosB, p-ERK1/2, and p-c-Jun ser63, along with the decrease in p-c-Jun ser73, induced by L-dopa in 6-OHDA-treated rats were significantly reversed by pretreatment with CA. In addition, we used the model of SH-SY5Y cells to further examine the neuroprotective mechanisms of CA on L-dopa-induced cytotoxicity. SH-SY5Y cells were treated with CA for 18 h, and then co-treated with 400 μM L-dopa for the indicated time points. The results showed that pretreatment of CA attenuated the cell death and nuclear condensation induced by L-dopa. By the immunoblots, the reduction of Bcl-2, p-c-Jun ser73, and parkin and the induction of cleaved caspase 3, cleaved Poly (ADP-ribose) polymerase, p-ERK1/2, p-c-Jun ser63, and ubiquitinated protein by L-dopa were improved in cells pretreated with CA. In conclusion, CA ameliorates the development of LID via regulating the D1R signaling and prevents L-dopa-induced apoptotic cell death through modulating the ERK1/2-c-Jun and inducing the parkin. This study suggested that CA can be used to alleviate the adverse effects of LID for PD patients.